Productivity, profitability, nutrient uptake and soil health as influenced by establishment methods and nutrient management practices in transplanted rice (Oryza sativa) under hill ecosystem of North East India - KUMAR, RAKESH; KUMAR, MANOJ; KUMAR, AMIT; PANDEY, AVINASH (The Indian Journal of Agricultural Sciences, 2015)
To evaluate the effect of different crop establishment methods and nutrient management practices in transplanted rice (Oryza sativa L.) under hill ecosystem, a field experiment was conducted at Agricultural Research Farm of Indian Council of Agricultural Research, Research Complex for North Eastern Hill Region, Jharnapani, Medziphema during kharif season of 2011 and 2012.Three crop establishment methods, viz. SRI (system of rice intensification), ICM (integrated crop management) and CTR (conventionally transplanted rice) were kept in main plots and five nutrient management practices, viz. control, 100% recommended dose of fertilizer (RDF), 100% RDF + 5 tonnes rice straw/ha, 100% RDN through FYM and 100% RDN through FYM + 5 tonnes rice straw/ha were allotted to sub-plots in a split-plot design and replicated thrice. The result showed that number of panicles/m2, panicle length and test weight were recorded significantly higher under SRI followed by ICM and CTR, whereas, grain yield was recorded higher with ICM followed by SRI than CTR. Among the nutrient management practices, application of 100% RDF + 5 tonnes rice straw/ha recorded significantly higher yield attributes and grain yield of 4.61 and 4.73 tonnes/ha in year 2011 and 2012, respectively and which was followed by 100% RDN through FYM + 5 tonnes rice straw/ha. Higher nutrient uptake (NPK) by grain and straw as well as total uptake were recorded under ICM followed by SRI and CTR. Similarly, higher nutrient uptake by grain and straw was recorded with 100% RDF + 5 tonnes rice straw/ha. The Maximum gross income, net income, benefit: cost ratio were significantly higher in ICM followed by SRI and CTR. Similarly, the maximum gross income, net income and benefit: cost ratio was fetched with 100% RDF + 5 tonnes rice straw/ha followed by 100% RDF.